At the Confluence of Data Streams: Mapping Paired Social and Biophysical Landscapes on the Puget Sound's Edge. Issue 5 (2nd September 2016) - Norman, Karma C.; Safford, Thomas G.; Feist, Blake E.; Henly, Megan
ABSTRACT: We seek to expand interdisciplinary insights into coastal management by pairing survey data from the general public with attendant landscape data in the Puget Sound region. Our social survey gathered information regarding attitudes and perceptions of changing social and environmental conditions in the Puget Sound Basin as well as views regarding possible management interventions. We mapped the survey data to US zip code regions and spatially overlaid the survey response data with existing geospatial data layers of biophysical conditions. Using mixed-effects logistic regression we examine the relationships between urban development trajectories and individual views about both environmental problems and possible policy responses. We found significant relationships between people's responses and the physical conditions within their residence zip code, as well as social variables, which illustrated the importance of developing new analytical approaches that consider the relationships between both biophysical and social features and individual attitudes about coastal environmental concerns.